2010
DOI: 10.1089/hum.2009.191
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Busulfan Administration After Hematopoietic Stem Cell Gene Therapy Associated with a Dominant HDAC7 Clone in a Nonhuman Primate

Abstract: The risk of genotoxicity of retroviral vector-delivered gene therapy targeting hematopoietic stem cells (HSCs) has been highlighted by the development of clonal dominance and malignancies in human and animal gene therapy trials. Large-animal models have proven invaluable to test the safety of retroviral vectors, but the detection of clonal dominance may require years of follow-up. We hypothesized that hematopoietic stress may accelerate the proliferation and therefore the detection of abnormal clones in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“… 20 , 37 NHPs transplated with MLV-transduced CD34+ cells have developed clonal dominance proceeding to overt MDS and/or leukemia due to insertional mutagenesis. 21 , 22 , 43 Although overt leukemia with RV transduction of HSPCs in large animal models has been an infrequent event, 44 most studies involved follow-ups shorter than relevant for clinical trials, relatively low transduction efficiency (median of 5% gene marking), and did not clearly provide data demonstrating whether overt malignancy was preceded in time by a long period of detectable clonal expansion. Our group previously demonstrated effective LV gene transfer to repopulating NHP HSPCs and long-term polyclonal hematopoiesis, without evidence of marked clonal expansion, even utilizing a vector with an extremely strong internal viral promoter/enhancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 20 , 37 NHPs transplated with MLV-transduced CD34+ cells have developed clonal dominance proceeding to overt MDS and/or leukemia due to insertional mutagenesis. 21 , 22 , 43 Although overt leukemia with RV transduction of HSPCs in large animal models has been an infrequent event, 44 most studies involved follow-ups shorter than relevant for clinical trials, relatively low transduction efficiency (median of 5% gene marking), and did not clearly provide data demonstrating whether overt malignancy was preceded in time by a long period of detectable clonal expansion. Our group previously demonstrated effective LV gene transfer to repopulating NHP HSPCs and long-term polyclonal hematopoiesis, without evidence of marked clonal expansion, even utilizing a vector with an extremely strong internal viral promoter/enhancer.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity might be enhanced or clonal expansions accelerated by the application of proliferative stress post-transplant, for instance, with busulfan, which we have previously shown can induce clonal dominance. 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others then rapidly completed surveys of large numbers of insertions in monkeys and dogs, providing the first evidence in primary cells for a number of very important principles, including a pattern of integrations favoring expressed genes with both MLV- and lentivirus-based vectors, and transcription start sites for MLV-based vectors, 283 and marked over-representation of integrations in specific proto-oncogenes such as EVI1, MDS1, HDAC7 and others, in a manner suggesting in vivo selection. 282,288 The identification of EVI1/MDS1 as a particularly worrisome locus was prescient, as the CGD trial adverse events demonstrated a few years later. 246 Novel vectors were reported as having much less concerning integration patterns in large animal models, including human foamy virus 289 and avian leucosis sarcoma virus.…”
Section: Evaluation Of Insertional Genotoxicity Using Mouse Modelsmentioning
confidence: 99%
“…Negative selection strategies using in particular alkylating drugs place a significant stress upon hematopoietic system. However, as demonstrated by Xie et al, 2010, repetitive hematopoietic stress by busulfan administration in a nonhuman primate may rapidly lead to reduction of polyclonality and eventually to cytopenia. In addition, potential long term mutagenic effects of alkylating agents are largely unknown, thus adding more uncertainty as to correct assessment of risks and benefits of this strategy.…”
Section: Safety: Vector Genotoxicity Transposon Vectors and Other Ismentioning
confidence: 99%